Dietary Patterns and Risk of Esophageal Cancer Mortality: The Japan Collaborative Cohort Study. (17th August 2016) - Okada, Emiko; Nakamura, Koshi; Ukawa, Shigekazu; Sakata, Kiyomi; Date, Chigusa; Iso, Hiroyasu; Tamakoshi, Akiko
ABSTRACT: Several case-control studies have associated dietary patterns with esophageal cancer (EC) risk, but prospective studies are scarce. We investigated dietary pattern and EC mortality risk associations by smoking status. Participants were 26, 562 40- to 79-yr-old Japanese men, who enrolled in the Japan Collaborative Cohort Study between 1988 and 1990. Hazard ratios (HRs) and 95% confidence intervals (CIs) for EC mortality in nonsmokers and smokers were estimated using Cox proportional models. During follow-up (1988–2009), 132 participants died of EC. Using a baseline food frequency questionnaire and factor analysis, vegetable, animal, and dairy product food patterns were identified. EC risk decreased significantly with a higher factor score for the dairy product pattern (Ptrend = 0.042) and was more pronounced in smokers [multivariable HR (4th vs. 1st quartiles) = 0.57, 95% CI: 0.30, 1.09; Ptrend = 0.021]. Neither vegetable nor animal food patterns were significant overall; however, EC risk increased with a higher factor score for the animal food pattern in nonsmokers [multivariable HR (4th vs. 1st quartiles) = 6.01, 95% CI: 1.17, 30.88; Ptrend = 0.021], although the small number of events was a limitation. Our findings suggest a dairy product pattern may reduce EC risk in Japanese men, especially smokers.